Efficient production of wild-type lipase B from Candida antarctica in the cytoplasm of Escherichia coli - Van Tassel, L. (Lisette); Moilanen, A. (Antti); Ruddock, L. W. (Lloyd W.) (Elsevier, 2020)
Abstract Candida antarctica lipase B (CalB) is a very efficient catalyst and is used in a wide range of industries from food flavour to pharmaceutical, and biodiesel manufacturing. It has a high degree of enantioselective and regioselective substrate specificity and is stable over a wide range of biophysical conditions including pH, temperature and solvent conditions. High-level expression of biologically active wild-type CalB has been problematic, partly due to folding events. Consequently, focus has been on modified CalB, which has allowed orders of magnitude increase in yields of protein. However, these modifications alter the quaternary structure of the protein. Here we produce soluble wild-type CalB in high yields in the cytoplasm of E.coli using a catalyzed system for cytoplasmic disulfide bond formation both in shake flasks and in fermentation in chemically defined media. The CalB produced had the expected stereospecific activity and had a higher activity than CalB from a commercial source.